Uzņēmuma “X” konkurētspējas analīze un attīstības iespējas nākotnē - Ķiršakmene, Kristīne (Latvijas Universitāte, 2018)
Izvērtēt uzņēmuma „X” darbību un konkurētspēju, izstrādāt priekšlikumus konkurētspējas paaugstināšanai. Tika vērtēta uzņēmuma iekšēja vide, cenu veidojošie faktori un uzņēmuma finanšu analīze. Ārējā vide tiek apskatīti uzņēmuma konkurenti, piegādātāji un reglamentējošie normatīvie akti.Tiek veikts klientu apmierinātības pētījums. Uzņēmuma „X” un konkurentu datu izvērtēšana.

Evaluate the company "X" marketing environment, to draw up proposals for increasing competitiveness.The present paper consists of four chapters. It deals with the external environment of the company; the surveys are carried out for better understanding the costumers’ needs and wishes. The manufacturing environment of the enterprise, the factors which impact the price and the financial analysis of the enterprise. In the external environment are examined the concurrency of the enterprise, suppliers and regulatory acts. Examined the level of the satisfaction of the clients. The enterprises “X” examine its competitor data evaluation
The assessment of marketing environment and competitiveness of the company “X”
Keywords: Uzņēmējdarbības vadība; cena; finanšu analīze; konkurenti; klienti; normatīvie akti